Compensation of wavefront aberration introduced by DMDs’ operation principle - Lee, BR (Lee, Beom-Ryeol) ; Marichal-Hernández, JG (Marichal-Hernandez, Jose G.) ; Rodríguez-Ramos, JM (Rodriguez-Ramos, Jose M.) ; Venkel, T (Venkel, Tetiana) ; Son, JY (Son, Jung-Young) (ELSEVIER, Optical Materials, 2023)
The wavefront aberration introduced by both rhomb and square pixel Digital Micromirror Devices (DMDs) to the reconstructed images from the holograms displayed on them is visualized with a color phase map obtained from a Shack-Hartmann wavefront sensor. The aberration causes blurring and distortions in the reconstructed images. The map informs that the aberration is induced by the virtual shrinkage of pixels introduced by their rotation because 1) the aberration is appearing along the DMDs' pixel rotation directions and 2) the DMD with a bigger size pixel introduces more aberration than that with a smaller size pixel. It is also shown that the aberration can be minimized with use of a white beam. The white beam is a reflected beam from the no image loaded On-state DMDs' surfaces when a collimated illumination beam is normally incident to them. Nevertheless, when the phase maps are compensated by the white beam, the reconstructed images become more distinguished and identified for both DMDs.
Keywords: Reconstructed image, Holograms, Rhomb and square pixel DMD, Shack-hartmann wavefront sensor, Color phase map, Wavefront aberration